Switch of Intravitreal Therapy for Macular Edema Secondary to Retinal Vein Occlusion from Anti-VEGF to Dexamethasone Implant and Vice Versa - Amelie Pielen; Anima Desiree Bühler; Sonja Ute Heinzelmann; Daniel Böhringer; Thomas Ness; Bernd Junker (Journal of Ophthalmology)
Purpose. To evaluate the anatomical and functional outcome of intravitreal dexamethasone implant for macular edema secondary to central (C) or branch (B) retinal vein occlusion (RVO) in patients with persistent macular edema (ME) refractory to intravitreal antivascular endothelial growth factor (VEGF) treatment compared to treatment naïve patients and to dexamethasone-refractory eyes switched to anti-VEGF. Methods. Retrospective, observational study including 30 eyes previously treated with anti-VEGF (8 CRVO, 22 BRVO, mean age 69 ± 10 yrs), compared to 11 treatment naïve eyes (6 CRVO, 5 BRVO, 73 ± 11 yrs) and compared to dexamethasone nonresponders (2 CRVO, 4 BRVO, 69 ± 12). Outcome parameters were change in best-corrected visual acuity (BCVA) and central foveal thickness (CFT) measured by spectral-domain optical coherence tomography. Results. Mean BCVA improvement after switch to dexamethasone implant was 4 letters (p=0.08), and treatment naïve eyes gained 10 letters (p=0.66), while we noted no change in eyes after switch to anti-VEGF (p=0.74). Median CFT decrease was most pronounced in treatment naïve patients (−437 μm, p=0.002) compared to anti-VEGF refractory eyes (−170 μm, p=0.003) and dexamethasone-refractory eyes (−157, p=0.31). Conclusions. Dexamethasone significantly reduced ME secondary to RVO refractory to anti-VEGF. Functional gain was limited compared to treatment naïve eyes, probably due to worse BCVA and CFT at baseline in treatment naïve eyes.